Pengaruh Kepemimpinan, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Pendapatan Wilayah Makassar II Badan Pendapatan Daerah Provinsi Sulawesi Selatan - Utari Nur Umrah; Abdul Rahman Mus; Aryati Arfah (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
Abstract This study aims to examine the influence of leadership, work motivation, and work environment on employee performance at the Revenue Office of Makassar Region II, Regional Revenue Agency of South Sulawesi Province. The data in this study were obtained from employees at the Revenue Office of Makassar Region II in 2025 who were willing to participate as respondents. This research used primary data obtained through direct field research by distributing questionnaires to respondents. The sampling technique applied was the census method due to the relatively small sample size, where the entire population consisting of only 57 employees was used as the sample. Data analysis was conducted using descriptive statistical analysis and SPSS 26.0. Based on the research results, it can be concluded that leadership, motivation, and work environment have a positive and significant effect on employee performance. The better the leadership implemented, the higher the motivation provided, and the more supportive the work environment, the better the employees’ performance will be, as they feel valued, enthusiastic, and able to work with focus and productivity in a comfortable and conducive atmosphere. Leaders who are firm yet supportive can foster a sense of appreciation and work loyalty, strong motivation encourages enthusiasm and commitment in completing tasks, and a favorable work environment enhances concentration and work spirit. Keywords:Leadership, Motivation,Worknvironment, Employee Performance